2007
DOI: 10.4319/lom.2007.5.233
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the stable isotope ratio of dissolved N2 in 15N tracer experiments

Abstract: Stable isotope addition experiments seeking to trace the denitrification of combined forms of nitrogen (N) to gaseous N 2 in aquatic environments typically need to measure the stable isotope ratio of dissolved nitrogen gas. This measurement presents challenges because of the potential for contamination of samples by N in air, and because field experiments conducted in situ often do not produce a marked enrichment in the isotope ratio of the N 2 pool. Field experiments also require numerous samples, sometimes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…Samples for the determination of δ 15 N 2 were collected according to Hamilton and Ostrom (2007); briefly, dissolved gases were equilibrated with a He atmosphere, and the headspace was transferred into a pre-evacuated 12 mL Exetainer (Labco Ltd, Lampeter, Ceredigion, UK). Samples for the analysis of dissolved N 2 concentrations were siphoned into 12 mL Exetainers to overflowing and amended with 200 µL of saturated ZnCl 2 solution to halt biological activity.…”
Section: Sediment Microbial N Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for the determination of δ 15 N 2 were collected according to Hamilton and Ostrom (2007); briefly, dissolved gases were equilibrated with a He atmosphere, and the headspace was transferred into a pre-evacuated 12 mL Exetainer (Labco Ltd, Lampeter, Ceredigion, UK). Samples for the analysis of dissolved N 2 concentrations were siphoned into 12 mL Exetainers to overflowing and amended with 200 µL of saturated ZnCl 2 solution to halt biological activity.…”
Section: Sediment Microbial N Removalmentioning
confidence: 99%
“…The headspace was analyzed by a gas chromatograph interfaced to an electron capture detector (GC-ECD; Shimadzu greenhouse gas analyzer GC-2014, Shimadzu Scientific Instruments, Columbia, MD, USA) for N 2 O concentration. The dissolved concentration was calculated based on the headspace equilibrium concentration (Hamilton and Ostrom, 2007).…”
Section: Sediment Microbial N Removalmentioning
confidence: 99%
“…For LINX II, interlaboratory comparisons of some particularly challenging analyses (e.g., 15 N tracer in dissolved N 2 and N 2 O gases) revealed that samples sent to some contract laboratories were not analyzed with the needed accuracy and precision. These challenges led to new and improved analytical methods and the decision to use a single laboratory at Michigan State University for N 2 analyses (Hamilton and Ostrom 2007), but LINX II data would have been more robust had analytical issues been identified earlier in the project. This experience underscores the importance of submitting known blind samples to any contract laboratories early in the experiment.…”
Section: Strategies For Successful Collaboration: Why Was Linx Succesmentioning
confidence: 99%
“…In addition, the 1 st y of LINX II data showed that existing methods for detecting tracer 15 N in N 2 at low concentrations were inadequate. New methods were developed and reported at LINX meetings prior to their publication (Hamilton and Ostrom 2007). These 2 examples of early adoption of new methods illustrate the need for ongoing communication, that early-career researchers often have important ideas to contribute, and that adaptive research approaches are necessary in large collaborative projects.…”
Section: Good Leaders Collaborators Planning and Communicationmentioning
confidence: 99%
“…Dissolved gases were extracted using a static headspace equilibrium method (Hamilton & Ostrom 2007) ), thereby facilitating comparison of the flux rates. In the case of dissolved N 2 , we used the atmospheric equilibrium concentration at the temperature of the sampling depth.…”
Section: Hydrochemical and Isotopic Measurementsmentioning
confidence: 99%